ANALISIS BIBLIOMETRIK KEUANGAN ENTREPRENEURIAL - Maulana, Yogi Sugiarto (Universitas Muhammadiyah Luwuk Banggai, 2023)
In this paper we conduct a systematic analysis of the development trend on entrepreneurial finance based on scientific publications data base at scopus.com. Objectives of the study are mapping scientific structure of entrepreneurial finance through scientometric analysis. We use the mapping knowledge domain software tools VOSviewer 1.6.12. We ï¬rst present the descriptive information, namely annual numbers of articles, source of publications, productive authors, origin countries, and main research affiliations as well as the source publications on entrepreneurial finance studies. We also report the collaborations among the main authors and countries using co-authorship analysis.